2014
DOI: 10.1016/j.virol.2014.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a macrophage-tropic SIV envelope glycoprotein variant in blood from early infection in SIVmac251-infected macaques

Abstract: Macrophages play an important role in HIV/SIV pathogenesis by serving as a reservoir for viral persistence in brain and other tissues. Infected macrophages have been detected in brain early after infection, but macrophage-tropic viruses are rarely isolated until late-stage infection. Little is known about early variants that establish persistent infection in brain. Here, we characterize a unique macrophage-tropic SIV envelope glycoprotein (Env) variant from two weeks post-infection in blood of an SIVmac251-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 90 publications
1
21
0
Order By: Relevance
“…However, an Env containing only the iMac239 gp120 changes, while CD4 independent, remained highly neutralization resistant, similar to parental SIVmac239. Similar findings were reported by Yen and coworkers, in which the loss of a glycosylation site in the SIVmac239 V2 loop (Asn-173) conferred the ability to infect macrophages in the context of cell-to-cell transmission while retaining the neutralization-resistant phenotype of SIVmac239 (59,60). In addition to indicating that CD4 independence and enhanced neutralization sensitivity can be dissociated, our findings also suggest that changes in the gp41 ectodomain that arose with iMac239's CD4 independence contribute to its neutralization sensitivity.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, an Env containing only the iMac239 gp120 changes, while CD4 independent, remained highly neutralization resistant, similar to parental SIVmac239. Similar findings were reported by Yen and coworkers, in which the loss of a glycosylation site in the SIVmac239 V2 loop (Asn-173) conferred the ability to infect macrophages in the context of cell-to-cell transmission while retaining the neutralization-resistant phenotype of SIVmac239 (59,60). In addition to indicating that CD4 independence and enhanced neutralization sensitivity can be dissociated, our findings also suggest that changes in the gp41 ectodomain that arose with iMac239's CD4 independence contribute to its neutralization sensitivity.…”
Section: Discussionsupporting
confidence: 88%
“…Because CD4-independent viruses are characteristically neutralization sensitive, it is likely that they are strongly selected against during typical pathogenic infection (32,48,49,97). Recent publications by Yen et al have suggested that CD4-independent entry serves as a mechanism of cell-cell viral spread in tissue macrophages, which is more efficient and can shield virus from neutralizing antibodies than cell-free transmission, thereby allowing CD4-independent variants to circulate in compartments such as the brain (59,60). Interestingly, primary isolates of HIV-2, which is less pathogenic than HIV-1 (reviewed in reference 98), have been reported to exhibit CD4 independence in vitro (61,99).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically early models used rhesus macaques (RM) or pigtail macaques (PM) and different viral clones or swarms that resulted in immune suppression (AIDS) macrophage tropism for CNS infection, and SIV encephalitis (SIVE) in approximately 30 percent of the animals in RM and higher percentages of PM [8](Table 1). More recently, immune modulation (depletion) of CD4 and CD8 T lymphocytes, and/or serial passage of virus through monkeys for enhanced macrophage replication and neurotropism have been used [6,911] (Table 1). One model uses mAb depletion of CD8 lymphocytes and infection with the viral swarm SIVmac251.…”
Section: Non-human Primate Models Of Neuroaidsmentioning
confidence: 99%
“…Hirsch and colleagues used a serially passaged SIVSmE543 and obtained SIVsm804E that established infection of the CNS early and resulted in a high incidence of SIVE. Gabuzda and collaborators similarly identified a macrophage tropic SIV env glycoprotein variant also found in the blood early in infection found in early infection of SIV251 infected animals, and made a molecular clones that enters the CNS early after inoculation and results in a high degree of SIVE [10,11](Table 1). The viral sequence data from these two models are discussed below.…”
Section: Non-human Primate Models Of Neuroaidsmentioning
confidence: 99%